Performance of a no-tillage seeder, in two soils with different types of vegetable coverages - Oliveira, Milson Lopes de; Vieira, Luciano Baião; Mantovani, Evandro Chartuni; Souza, Caetano Marciano de; Dias, Gutemberg Pereira (Pesquisa Agropecuaria Brasileira, 2000)
The performance of a no-tillage seeder, version soybean and corn was evaluated under two classes of soil, a cambic Red-Yellow Podzolic terrace phase and a Red-Yellow Latosol, at Zona da Mata, MG. The machine was tested under three different vegetable coverages in two work speeds. During test, tractor and planter slipping, fuel consumption and the power required by the machine, distribution fertilizer, and seeds damage were evaluated. After planting, the number of seeds by hectare, final stand, planting depth and seed longitudinal distribution, were also evaluated. The uniformity of longitudinal distribution was measured for percentage of admissible spacing, pair distribution, failures on distribution and by coefficient variation of seed spacing. The demand of power was higher on podzolic, due to its higher density and resistance to penetration. Regardless of the type of treatment, the number of seeds distributed and the final stand obtained showed no significant difference and the depth average obtained in the test was close to the values foreseen in the control. The seeds distributed were not affected by dosage mechanism. The analysis of variance indicated no significant variation between the values of admissible spacing, the pair distribution and failures.